The role of echocardiography in the embolic stroke of undetermined source. Issue 8 (August 2020) - Danese, Alessandra; Mugnai, Giacomo; Prevedello, Francesca; Morra, Michele; Bilato, Claudio
Abstract : N/A: Echocardiography plays an important role both in the diagnosis and the treatment/prevention of embolic stroke of undetermined source and should be performed as soon as possible for preventing ischemic stroke recurrencies, which occur more frequently during the first week after the first ischemic event. Early identification of the cause of a transient ischemic attack or stroke is indeed a primary goal for the neurologist in the Stroke Unit and requires specific diagnostic strategies. Echocardiography, together with other diagnostic tools such as carotid and transcranial ultrasounds, provides this information promptly. In particular, echocardiography might be able to detect the main sources of the embolic stroke, such as atrial fibrillation, ventricular akinesia, aortic atheroma plaques and/or cardiac shunts. The present review discusses the importance and the practical role of echocardiography as a crucial diagnostic tool for detecting the main source of emboli in the setting of the acute stroke.